Wanprestasi oleh Koperasi Simpan Pinjam: Bagaimana Dampak Hukumnya? - Martin, Brian (Legal Spirit, 2024)
The development of the national economy and the changes that occur in the business environment, including the savings and loan cooperative unit, which is directed to always encourage and play an active role in increasing the income of its members in order to be able to overcome existing social inequality. Cooperatives are a joint business entity that struggles in the economic field by taking the right and steady path with the aim of freeing itself from the economic difficulties generally suffered by its members. However, in reality, this cooperative has not been maximized in controlling credit so that the ability to generate Residual Income (SHU) is still less effective and must enter the realm of court because of defaulting on its customers. Therefore, this research will analyze legal protection in the event of default by the company in this context is the Cooperative. This research is normative (legal) research. The results of this study conclude that the Cooperative Law does not specifically mention legal protection for customer funds while for customers the protection is seen in article 7 and article 8 of Government Regulation Number 33 of 1998 concerning Participation Capital in Cooperatives and the protection of customers is not regulated with certainty so that regulations are needed to resolve defaults committed by business actors of Savings and Loan Cooperatives.